Tendency of Discreteness of the Solar Amplitude and Intercycle Relatedness - Akio Yoshida; Ryan Sayre (Advances in Astronomy)
We suggest that the average of the sunspot number (SSN) over a cycle offers a more appropriate index than the maximum value of the SSN in the evaluation of the activity of solar cycles. We then show that the average SSN has a tendency to take discrete values, that is, integral multiples of 20. This remarkable finding is supported by the fact that SSNs around the maximum are likely to take some particular values. Further, it is shown that there exists a positive correlation in the amplitude between even-numbered cycles and succeeding odd-numbered cycles and an inverse correlation between (2𝑛+1) cycles and (2𝑛+4) cycles where 𝑛 represents an integer. If these two correlations are combined, it turns out that there exist two mutually independent series of cycles which do not mix or merge.